SISTEM MONITORING KEKERUHAN AIR MENGGUNAKAN JARINGAN WIRELESS SENSOR SYSTEM BERBASIS WEB - Khanif Pramusinto; Suryono Suryono (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Turbidity in the water was not the nature of the water harmful but can cause concern contained impact of chemical compounds that are harmful to living things. Turbidity caused by suspended matter or insoluble. Water that exists today can not be separated from the insoluble particle pollution such as sand, mud, organic and inorganic chemicals that have an impact on organisms in the water. Wireless sensor system with a telemetry system can be a solution of the measurements performed remotely from the turbidity of the water. System monitoring turbidity in this study consisted of a water turbidity sensor that is connected to the microcontroller ATSAM3X8E. The results of the turbidity sensor converted by ADC microcontroller. Data read has been converted into a digital converted into the turbidity value by the microcontroller. Data communication systems that use serial communication between the microcontroller with a personal computer (PC) and data acquisition results displayed on acquisition applications on the PC and then stored into the database. Data acquisition results turbidity has an average division of ± 68 NTU. The data was transmitted from the station Remote Terminal Unit (RTU) to station Terminal Control Unit (CTU) with telemetry technique used a WiFi network that can be accessed through a web browser on a PC CTU and can displayed data in real-time in the form of a table.